DETERMINAN PERILAKU KEPATUHAN PAJAK PADA PROFESI DOKTER - Lalu Hakiki; Taufik Raharjo (Universitas Cenderawasih, 2018)
This study aims to analyze the factors that influence the behavior of doctor’s tax compliance with the approach to compliance behavior models. This study was conducted in Indonesia. Data collection in this research is using questionnaire where respondent in this research is doctors who served in several regions in Indonesia. The sampling technique used in this study is convenience sampling methoded. The number of research samples taken as many as 109 respondents. This research uses Partial Least Square (PLS) analysis technique. The results of this study indicate that the variables that have the greatest influence on the behavior of doktor compliance are intention, attitude, and taxpayer identity variables.